Supervision : Building Public Confidence in Mandatory Funded Pensions - Whitehouse, Edward (World Bank, Washington, DC, 2012)
The regulation and supervision of individual pension accounts has been a neglected issue. In contrast, much has been written on financing the transition to funded pensions and the design of benefits. Yet effective regulation and efficient supervision are crucial to the success of pension reform. This note explores six issues in the design of a supervisory regime. It makes some comparisons between the performances of agencies in different countries and looks at four important areas of supervision : institutional and financial controls, and membership and benefits procedures. Some of the conclusions presented in this note are : professional expertise, transparency and perceived independence of supervisory agencies is essential to the success of pension reform; in countries where existing regulation is weak or ineffective, a new, separate agency is probably best placed (but not certain) to avoid repeating past failures; administrative independence is similarly preferable; salaries must be competitive with the private sector (and remain so) to recruit qualified personnel from public and private sectors and to limit corruption risk; separation of regulation and supervision can help limit the risk of regulatory capture.